2010
DOI: 10.20870/oeno-one.2010.44.3.1470
|View full text |Cite
|
Sign up to set email alerts
|

Vineyard altitude and mesoclimate influences on the phenology and maturation of Cabernet-Sauvignon grapes from Santa Catarina State

Abstract: <p style="text-align: justify;">Santa Catarina State (SC) is a new grape growing region in Southern Brazil where 300 ha have been planted with <em>Vitis vinifera</em> L. since 2000. The annual production of this region is 3,944 tons of grapes and 1,549,000 liters of wine.</p><p style="text-align: justify;"><strong>Aims</strong>: To evaluate the influence of climate and vineyard altitude on the phenology and ripening as well as the suitability of five new grape growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
2
24
1
1
Order By: Relevance
“…Regarding the question posed at the beginning of this study, one may infer that the significant trends detected in the Tmin and DTR series (Table 4) support the hypothesis of the presence of climate change that may affect the wine production of the eastern part of the State of São Paulo (Falcão et al, 2010;Giovaninni and Manfroi, 2009). This hypothesis is also consistent with the results presented in table 5.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Regarding the question posed at the beginning of this study, one may infer that the significant trends detected in the Tmin and DTR series (Table 4) support the hypothesis of the presence of climate change that may affect the wine production of the eastern part of the State of São Paulo (Falcão et al, 2010;Giovaninni and Manfroi, 2009). This hypothesis is also consistent with the results presented in table 5.…”
Section: Resultsmentioning
confidence: 52%
“…The abovementioned evidences of warming trends observed in virtually all world's highest quality vine-producing regions of the Globe supports the assumption that the wine industry may be required to find new locations for viticulture (Falcão et al, 2010). Accordingly, we posed the following question: Is there any evidence of climate change that may impact the wine production of non-traditional areas?…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The study findings for Samsun are similar to those reported by Bois et al (2008) for Bordeaux, which has a moderately warm climate, with a mean annual temperature of 13.8°C and an annual rainfall of 930 mm. The Rhône Valley in France and São Joaquim in Brazil were also reported to have a Region III WI classification (Falcao et al, 2010). Similarly, the warmest areas in Italy were classified as Region III and include the vicinity of Garda Lake, the Adige River Valley and low-elevation regions of Vicenza, Treviso and Pordenone.…”
Section: Winkler Index-wi (Growing Degree Days)mentioning
confidence: 99%
“…GRIS et al (2010) consideram 10 ºC de amplitude térmica adequado para a fenologia e a maturação das uvas nas regiões de altitude de Santa Catarina. FALCÃO et al (2010) avaliaram a influência da altitude e de fatores mesoclimáticos na fenologia e maturação da Cabernet Sauvignon nessas regiões, e perceberam que a amplitude térmica é mais significativa nos vinhedos de elevada altitude localizados em vales, do que naqueles localizados em planaltos. Esses autores concluíram ainda que a quantidade de noites frias é mais importante do que a amplitude térmica para a qualidade do vinho.…”
Section: Caracterização Agronômicaunclassified